HEAT-TRANSFER BY OSCILLATING FLOW IN A CIRCULAR PIPE WITH A SINUSOIDAL WALL TEMPERATURE DISTRIBUTION - LEE, DY; PARK, SJ; RO, ST (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
A theoretical investigation was carried out on the heat transfer characteristics of an oscillating flow in a circular pipe. In contrast with the earlier studies on similar topics, the nonlinear temperature boundary condition, more precisely sinusoidal temperature distribution, was considered in this study. For this specific case, the present study revealed the existence of two important parameters and the occurrence of three distinct regimes. The detailed characteristics of the section-averaged temperature, the wall heat flux and the Nusselt number are presented and addressed. Since the general distribution of the temperature at the cylinder wall can be expanded in a Fourier Series, it is of fundamental nature to analyze the case with sinusoidal temperature distribution. The superposition principle would then allow for the use of present basic analysis for more practical systems.
Keywords: CONDUCTION; DIFFUSION; FLUIDS; TUBES